1997
DOI: 10.1002/(sici)1097-4547(19970615)48:6<588::aid-jnr12>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor delays oligodendrocyte differentiation and axonal myelination in vivo in the anterior medullary velum of the developing rat

Abstract: The AA dimeric form of platelet-derived growth factor (PDGF-AA) is implicated in the differentiation of cells of the oligodendrocyte lineage, which express PDGF receptors of the alpha subunit type (PDGF-alphaR). In the present study, we show that a single injection of PDGF-AA into the cerebrospinal fluid of neonatal rats delays oligodendrocyte differentiation and interrupts the progress of myelination in the anterior medullary velum (AMV), a white matter tract roofing the IVth ventricle of the brain. PDGF-AA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…PDGF-AA, which was measured in the gut hormone panel, has an important role in myelin maintenance [93]. PDGF-A receptor is regulated by β-FGF [93], and PDGF regulates oligodendrocyte progenitor cells functions, including myelination [94,95]. Therefore, the reduced levels of PDGF in AD correspond with the previously demonstrated early loss of white matter and hypomyelination in this disease [96,97].…”
Section: Discussionmentioning
confidence: 90%
“…PDGF-AA, which was measured in the gut hormone panel, has an important role in myelin maintenance [93]. PDGF-A receptor is regulated by β-FGF [93], and PDGF regulates oligodendrocyte progenitor cells functions, including myelination [94,95]. Therefore, the reduced levels of PDGF in AD correspond with the previously demonstrated early loss of white matter and hypomyelination in this disease [96,97].…”
Section: Discussionmentioning
confidence: 90%
“…We combined ChABC with administration of EGF, bFGF and PDGF-AA to enhance the survival of transplanted NPCs and direct their fate into oligodendrocytes. PDGF-AA is growth factor secreted by astrocytes in the CNS that promotes the proliferation of neural progenitors and stimulates the differentiation of oligodendrocytes [44], [45], and is also implicated in the survival of and migration of newly formed oligodendrocytes [46], [47]. Moreover, PDGF, in synergy with bFGF, regulates the proliferative response of adult oligodendrocyte progenitors [48], [49], [50].…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the two differentiation pathways in more detail, PDGF and bFGF can be seen to enhance immature OL proliferation and delay differentiation to mature OL in both cell types. For instance, studies on primary OL have shown that PDGF can delay OL differentiation when injected into the cerebrospinal fluid of neonatal rats (Butt et al, 1997). As well, decreases in PDGF signalling have been shown to correspond to an exit of proliferative, immature OL from the cell cycle, and anti-PDGF antibodies have been shown block OL mitosis (Dutly and Schwab, 1991;Calver et al, 1998).…”
Section: A Comparison Of Primary Ol and Cg-4mentioning
confidence: 99%